Changing boreal methane sources and constant biomass burning during the last termination - Fischer, Hubertus; Behrens, Melanie; Bock, Michael; Richter, Ulrike; Schmitt, Jochen; Loulergue, Laetitia; Chappellaz, Jerome; Spahni, Renato; Blunier, Thomas; Leuenberger, Markus; Stocker, Thomas F. (Nature, 2008)
International audience Past atmospheric methane concentrations show strong fluctuations in parallel to rapid glacial climate changes in the Northern Hemisphere superimposed on a glacial–interglacial doubling of methane concentrations. The processes driving the observed fluctuations remain uncertain but can be constrained using methane isotopic information from ice cores. Here we present an ice core record of carbon isotopic ratios in methane over the entire last glacial–interglacial transition. Our data show that the carbon in atmospheric methane was isotopically much heavier in cold climate periods. With the help of a box model constrained by the present data and previously published results we are able to estimate the magnitude of past individual methane emission sources and the atmospheric lifetime of methane. We find that methane emissions due to biomass burning were about 45 Tg methane per year, and that these remained roughly constant throughout the glacial termination. The atmospheric lifetime of methane is reduced during cold climate periods. We also show that boreal wetlands are an important source of methane during warm events, but their methane emissions are essentially shut down during cold climate conditions.